Enhancing the Replication Potential of Smart Lighting Projects - Madis Talmar; A. Georges L. Romme; Rianne Valkenburg (Smart Cities, 2022)
To address major threats to the sustainability and quality of life in urban settings, many municipalities have started exploring routes toward smarter cities to, for example, lower their energy consumption and carbon footprint. These explorations, in the form of living labs or other pilot projects, often suffer from major problems in scaling up the initial try-outs. In this study, we identify the mechanisms that facilitate the diffusion of smart city solutions, which are developed with public funds but typically lack dedicated resources to spur the diffusion of these solutions within the same municipality as well as toward other municipalities. We introduce the construct of embedded replication potential, defined as the capacity of an original project to be either scaled up locally or replicated elsewhere. Subsequently, empirical findings from a study of smart lighting projects in several municipalities in northwestern Europe serve to develop a checklist-based tool for assessing the embedded replication potential of an initial project. This tool can also be used to assess the replication potential of other smart city projects.